2012
DOI: 10.1111/j.1439-0531.2012.02088.x
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Roles of Progesterone Receptor (PGR) in Ovulation, Oocyte Developmental Competence and Oviductal Transport in Mammalian Reproduction

Abstract: Contents Progesterone is critical for successful ovulation in the ovary and for the multi‐faceted role of the oviduct in mammalian reproduction. Its effects are mediated by progesterone receptor (PGR), which is highly expressed in the ovary, specifically granulosa cells of preovulatory follicles in response to the luteinizing hormone (LH) surge that occurs just prior to ovulation, and in the oviduct, predominantly luminal epithelial cells but also muscle cells. This review will summarize research which shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 108 publications
1
52
0
Order By: Relevance
“…This influx is postulated to occur in part through LH mediated pathways that increase vasodilation and vascular permeability, allowing the transmigration of leukocytes from the blood vessels to the preovulatory follicle (25). Mice lacking genes that are responsible for the LH mediated inflammatory reaction, such as the PGR (26,27), PTGS2 (28), or increased vasodilation, such as endothelin 2 (29), fail to ovulate or have reduced ovulatory capacity (30). However, the importance of leukocytes in the ovulatory process is evident from observations that the number of oocytes released increased approximately 3-fold when leukocytes were added to perfused rat ovaries (4), whereas depletion of leukocytes from the blood decreased the number of ovulations (3,5).…”
Section: Discussionmentioning
confidence: 98%
“…This influx is postulated to occur in part through LH mediated pathways that increase vasodilation and vascular permeability, allowing the transmigration of leukocytes from the blood vessels to the preovulatory follicle (25). Mice lacking genes that are responsible for the LH mediated inflammatory reaction, such as the PGR (26,27), PTGS2 (28), or increased vasodilation, such as endothelin 2 (29), fail to ovulate or have reduced ovulatory capacity (30). However, the importance of leukocytes in the ovulatory process is evident from observations that the number of oocytes released increased approximately 3-fold when leukocytes were added to perfused rat ovaries (4), whereas depletion of leukocytes from the blood decreased the number of ovulations (3,5).…”
Section: Discussionmentioning
confidence: 98%
“…Steroid hormones play major roles in reproduction (Mulac-Jericevic & Conneely, 2004;Akison & Robker, 2012), notably during gestation (Simpson & MacDonald, 1981). For instance the elevation of progesterone plasma concentration is essential for the establishment and maintenance of pregnancy (Soûles, 1989;Baird et al, 1997;Magiakou et al, 1997;Ferin, 1999;Ark, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice and in human have demonstrated the critical role of nPR in ovulation910. Female mice lacking nPR exhibit anovulation, impaired sexual behavior, uterine dysfunction, impaired ductal branching morphogenesis and lobuloalveolar differentiation of the mammary gland11121314.…”
mentioning
confidence: 99%